2010
DOI: 10.1007/s11244-010-9551-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acid Modification on Selective Phenol Hydrogenation Over Pd/Activated Carbon Catalysts

Abstract: The influence of the acid treatment on cyclohexanone selectivity of phenol hydrogenation over Pd on active carbon was studied in liquid phase reaction and by temperature-programmed desorption. Acid treatment of activated carbon led to an increased cyclohexanone/cyclohexanol ratio. Acid modification of the carbon support enriched the electron density of Pd, and enhanced the desorption of the phenoxy species, which resulted in improved cyclohexanone selectivity in phenol hydrogenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 34 publications
2
23
0
1
Order By: Relevance
“…Prior research on the one‐step hydrogenation of phenol to cyclohexanone showed that cyclohexanone is, under standard conditions, a reactive intermediate and was easily further hydrogenated to cyclohexanol, and high selectivity (>95 %) at elevated conversion (>80 %) is a great challenge 165. 187, 188 Pd@mpg‐C 3 N 4 was shown to be highly active in hydrogenation and promoted the selective formation of cyclohexanone even under an atmospheric pressure of hydrogen and under aqueous conditions. For example, the catalytic hydrogenation of phenol with 5 mol % Pd@mpg‐C 3 N 4 in water at 65 °C proceeded with 99 % conversion in 2 h and more than 99 % selectivity for cyclohexanone.…”
Section: Applications Of Carbon Nitridementioning
confidence: 99%
“…Prior research on the one‐step hydrogenation of phenol to cyclohexanone showed that cyclohexanone is, under standard conditions, a reactive intermediate and was easily further hydrogenated to cyclohexanol, and high selectivity (>95 %) at elevated conversion (>80 %) is a great challenge 165. 187, 188 Pd@mpg‐C 3 N 4 was shown to be highly active in hydrogenation and promoted the selective formation of cyclohexanone even under an atmospheric pressure of hydrogen and under aqueous conditions. For example, the catalytic hydrogenation of phenol with 5 mol % Pd@mpg‐C 3 N 4 in water at 65 °C proceeded with 99 % conversion in 2 h and more than 99 % selectivity for cyclohexanone.…”
Section: Applications Of Carbon Nitridementioning
confidence: 99%
“…Ein organischer Halbleiter, der photochemisch Wasserstoff freisetzt, kann natürlich auch die umgekehrte Reaktion katalysieren, nämlich die Hydrierung von Doppelbindungen. Wegen der schon oben diskutierten kinetischen Hemmung, organische kovalente Bindungen zu spalten, ist es hilfreich, [165,187,188] [165,189] Das katalytische System Pd@mpg-C 3 [130] Der Katalysator ist hoch aktiv und ergibt eine hohe Ausbeute der entsprechenden Ester in sehr kurzer Zeit. Die gleiche Gruppe zeigte auch, dass die Einkapselung von Au-Nanopartikeln in N-haltigen Kohlenstoffen einen hochaktiven, selektiven und wiedergewinnbaren Katalysator ergibt, der Benzaldehyd, Piperidin und Phenylacetylen zum entsprechenden Propargylamin kondensieren kann, eine Reaktion, die anderwärts nur von sehr starken Basen wie Butyllithium, Organomagnesium-Reagentien oder Lithiumdiisopropylamid katalysiert wird (Schema 8).…”
Section: Anwendung In Hydrierungenunclassified
“…Similar observations have also been reported. [35] As for hydrochloric acid treatment, the surface area and the pore volumes are generally enhanced due to the removal of the ash during acid treatment. [32,36]…”
Section: Surface Area Of Samples Of Ac Supportsmentioning
confidence: 99%